(untitled) (Baghdad Science Journal, 2011)
This study was conducted to evaluate the efficacy of different techniques for extraction and purification of Tomato yellow leaf curl virus (TYLCV). An isolate of the virus free of possible contamination with other viruses infecting the same host and transmitted by the same vector Bemisia tabaci Genn. was obtained. This was realized by indicator plants and incubation period in the vector. Results obtained revealed that the virus infect Nicotiana glutinosa without visible symptoms, while Nicotiana tabaccum var. White Burley was not susceptible to the virus. The incubation period of the virus in the vector was found to be 21 hrs. These results indicate that the virus is TYLCV. Results showed that Butanol was more effective in clarification the sap and eliminate of plant proteins and chlorophyll. The use of citrate buffer at pH 8 amended with reducing agents and EDTA to prevent the oxidation of phenolic compound was found to be suitable in maintaining the biological activity of the virus during extraction. The quantity of the virus obtained was 3.05 mg/100 gm leaves with absorption ratio of 1.4 at 260/280 nm which represent standard value for TYLCV.